SLOVENSKO JEZIKOSLOVJE, KNJIŽEVNOST IN POUČEVANJE SLOVENŠČINE. SLOVAR SLOVENSKEGA KNJIŽNEGA JEZIKA 16. STOLETJA. VELIKI MADŽARSKO-SLOVENSKI SPLETNI SLOVAR. Ur. Marko Jesenšek: Maribor: Univerzitetna založba Univerze, 2020. (Mednarodna knjižna zbirka Zora, 135). 399 str. - Nikolovski, Gjoko (Slavia Centralis, 2020)
The author of the article presents a new scientific monograph Slovene Linguistics, Literature and Teaching of Slovenian Language, Dictionary of the Slovene Literary Language of the 16th Century, The Great Hungarian-Slovene Online Dictionary, edited by the head of the research program no. P6-0156, Slovene Linguistics, Literature and Teaching of Slovenian Language, Marko Jesenšek.